Resilience and adherence to HAART in patients with HIV/AIDS at the Hospital San Juan Bautista de Huaral - Bedón López, Yaymi Lizbeth (2013)
This study aimed to determine the relationship between resilience and adherence to HAART (Highly active Antiretroviral Therapy) in a sample of patients from the San Juan Bautista de Huaral hospital. The nonrandom sample consisted of 64 patients with HAART at San Juan Bautista Hospital Huaral, whose ages ranged from 18 to 59 years. The instruments used were the Resilience Questionnaire (RS) and the Adherence Assessment Questionnaire. The results revealed that the participants have a High level of resilience and Medium level of adherence, we found a significant positive relation between resilience and adherence to HAART (r = 0.453, p <0.001) and a significant relationship between resilience factors: personal competence and self-acceptance and of life with adherence to TARGA, we also found a significant and positive relationship with the areas of social environment adhesion and lifestyle to the resilience level. However, areas such as work environment, health background and emotional aspect are not related to the level of resilience.